Unlocking the relationships between strategic planning, leadership and technology transfer competence: the mediating role of strategic quality management - Gulin Idil Sonmezturk Bolatan; Gölgeci, Ismail; Arslan, Ahmad; Tatoglu, Ekrem; Zaim, Selim; Gözlü, Sitki (Emerald, 2022)
Purpose This study aims to investigate the relationships between firms’ strategic planning (SP), leadership and technology transfer competence (TTC) by specifically incorporating the mediating role of strategic quality management (SQM). Design/methodology/approach This study performs structural equation modeling using AMOS on survey data collected from 200 Turkish firms operating in multiple industries and sectors. Findings This study finds that leadership in Turkish firms operating in multiple sectors is positively associated with SQM. This study further finds that SQM positively influences Turkish firms’ TTC and mediates the roles of SP and leadership in TTC. Research limitations/implications A key research implication from this study relates to the mediating role of SQM in TTC in an emerging economy context. This study highlights that SP and leadership can play an essential role in TTC through the mediating mechanism of SQM. Consequently, SQM emerges as a crucial linking pin in conveying the impact of quality management practices on technology transfer in emerging markets. Practical implications An essential managerial implication of this study relates to the critical roles of leadership, SP and SQM in TTC. For the managers of firms operating in a relatively uncertain emerging context such as Turkey, it is essential to adopt a supportive and empowering leadership style, where open communication and innovative activities are viewed positively and SQM is adopted holistically. Also, SP should be streamlined throughout the firm and followed by SQM to support TTC. Originality/value This paper links the technology (and knowledge) management and the strategy and leadership literature streams by focusing on the mechanisms of technology transfer and delving into the linkages between SQM, leadership, SP and TTC. It specifically presents SP and leadership as precursors to SQM in their joint influence on TTC. Accordingly, this research bridges technology, strategy and leadership research and provides a broader picture of technology transfer that encompasses the joint role of different processes in firms’ TTC.
Keywords: Leadership; Turkish firms; Strategic quality management; LeadershipStrategic quality managementStrategic planningTechnology transfer competenceTurkish firms; Technology transfer competence; Strategic planning; Strategic Quality Management; Strategic Planning; Turkish Firms; Technology Transfer Competence